2010
DOI: 10.2220/biomedres.31.105
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin expression of esophageal squamous cell carcinoma and its aggressive potential for lymph node metastasis

Abstract: Esophageal squamous cell carcinoma (ESCC) has been generally considered as one of the most aggressive cancers with poor prognosis. Vimentin is the major protein constituent of intermediate filaments in normal and neoplastic mesenchymal cells, and has been regarded as a marker of epithelial-mesenchymal transition (EMT). However, little is known about ESCC with vimentin expression as a marker of EMT. In this study, we analyzed vimentin expression in 129 cases of ESCC in order to elucidate whether vimentin expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 33 publications
4
30
0
1
Order By: Relevance
“…This is consistent with the established roles of EMT during ESCC progression, since reduced E-cadherin [16–20] with increased N-cadherin [21, 22] and vimentin [23, 24] expression would reduce cell adhesion, increase cell mobility, and ultimately enhance cell invasiveness and metastasis to form advanced stage tumors. However, we found no significant association between expression of any EMT marker in PTs and N-stage, a clinical lymph node metastasis parameter.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with the established roles of EMT during ESCC progression, since reduced E-cadherin [16–20] with increased N-cadherin [21, 22] and vimentin [23, 24] expression would reduce cell adhesion, increase cell mobility, and ultimately enhance cell invasiveness and metastasis to form advanced stage tumors. However, we found no significant association between expression of any EMT marker in PTs and N-stage, a clinical lymph node metastasis parameter.…”
Section: Discussionsupporting
confidence: 85%
“…In gastric cancers, vimentin expression was more associated with the invasive phenotype of gastric carcinoma and was suggested to play an important role in the metastasis of gastric carcinomas and serve as a prognostic marker in the detection of gastric cancers (81, 82). Analysis of esophageal squamous cell carcinoma samples from patients showed that vimentin expressing cells exhibit significantly higher incidence of lymph node metastasis (83). In HCC, vimentin expression was mainly associated with the metastatic HCC (84); however, in small HCC's, vimentin was detectable in the serum samples (66).…”
Section: Vimentin In Cancermentioning
confidence: 99%
“…Although its expression is more emphasized in the EMT process, it is equally possible that tumorigenic events including tumor cell migration and invasion are a consequence of vimentin over-expression in these cells, as most of the studies indicated a positive association of invasive phenotype to vimentin over-expression and showed a decrease in these characteristics upon knock-down of vimentin in vitro . Furthermore, vimentin's over-expression during metastasis (78, 83, 84, 101, 104) attracts much attention to further elucidate its role as a metastasis-promoter. However, these events are a result of fine tuning occurring in the cancer cells and vimentin might be acting as a scaffolding protein during signal transduction and promoting tumorigenic events in association with other tumor promoting oncogenes.…”
Section: Vimentin In Cancermentioning
confidence: 99%
“…It has been identified as a hallmark of metastasis in multiple tumors, connecting to plenty of transcriptional factors [36], [37], [38], [39]. miRNAs are also components of the cellular signaling circuitry that regulates the EMT program [40].…”
Section: Introductionmentioning
confidence: 99%